PEMAHAMAN PARA KEPALA DESA TERHADAP EKONOMI SYARIAH DI KECAMATAN PAMIJAHAN KABUPATEN BOGOR - Ade Alimudin (Institut Agama Islam Sahid Bogor, 2023)
The understanding of Islamic economics for the leader of village is very important especially for those who are Muslim because this is their field to fight and uphold the teachings of religion according to the guidance of the Qur'an and the Sunnah of the Prophet Muhammad. Based on this, benefits can be obtained including: (1) the realization of true Muslim integrity, (2) benefiting the world and the hereafter, (3) practicing Islamic economics including the value of worship because of carrying out Islamic law, (4) supporting the economic empowerment of the people, (5) supports the amar ma'ruf nahi mungkar movement by not engaging in usury practices which are prohibited by Islam. This research was conducted to determine the understanding of leader of village towards the Islamic economy in the Pamijahan sub-district with a total of 15 villages. The researcher conducted a survey of all leader of village s to obtain accurate data. After conducting the research level of understanding from the leader of village was obtained varied, but from these results the data was processed so that conclusions were drawn according to the results of the study. The background of each leader of village in terms of age, education, family, environment and sources of understanding makes different levels of understanding. During the research process, the researcher first prepares the research instruments needed such as interview materials, notebooks, documentation tools and questionnaires. The discussion in this study was carried out with a descriptive qualitative method. This researcs state is the leader of village in the Pamijahan sub-district has a high understanding of the Islamic economy. Judging from his background, all Islamic leader of village s have all received education both from the study of the environment and their experience of learning as students at Islamic boarding schools which makes them understand Islamic teachings and understand about Islamic economics, thus Islamic economics can be upheld as long as there is desire to do it